Embryonic pig pancreatic tissue transplantation for the treatment of diabetes. - Smadar Eventov-Friedman; Dalit Tchorsh; Helena Katchman; Elias Shezen; Anna Aronovich; Gil Hecht; Benjamin Dekel; Gideon Rechavi; Bruce R Blazar; Ilan Feine; Orna Tal; Enrique Freud; et al. (PLoS Medicine, 2006)
BACKGROUND:Transplantation of embryonic pig pancreatic tissue as a source of insulin has been suggested for the cure of diabetes. However, previous limited clinical trials failed in their attempts to treat diabetic patients by transplantation of advanced gestational age porcine embryonic pancreas. In the present study we examined growth potential, functionality, and immunogenicity of pig embryonic pancreatic tissue harvested at different gestational ages. METHODS AND FINDINGS:Implantation of embryonic pig pancreatic tissues of different gestational ages in SCID mice reveals that embryonic day 42 (E42) pig pancreas can enable a massive growth of pig islets for prolonged periods and restore normoglycemia in diabetic mice. Furthermore, both direct and indirect T cell rejection responses to the xenogeneic tissue demonstrated that E42 tissue, in comparison to E56 or later embryonic tissues, exhibits markedly reduced immunogenicity. Finally, fully immunocompetent diabetic mice grafted with the E42 pig pancreatic tissue and treated with an immunosuppression protocol comprising CTLA4-Ig and anti-CD40 ligand (anti-CD40L) attained normal blood glucose levels, eliminating the need for insulin. CONCLUSIONS:These results emphasize the importance of selecting embryonic tissue of the correct gestational age for optimal growth and function and for reduced immunogenicity, and provide a proof of principle for the therapeutic potential of E42 embryonic pig pancreatic tissue transplantation in diabetes.